Resting and TMS-EEG markers of treatment response in major depressive disorder: A systematic review - Strafella, Rebecca; Chen, Robert; Rajji, Tarek K.; Blumberger, Daniel M.; Voineskos, Daphne (Frontiers in Human Neuroscience, 2022)
Electroencephalography (EEG) is a non-invasive method to identify markers of treatment response in major depressive disorder (MDD). This review's objectives were the following: firstly, to report changes in EEG measures following MDD treatment; secondly, to compare changes in EEG measures between treatment responders and non-responders; thirdly, to identify whether EEG measures can predict treatment success. PubMed and EMBASE were searched from 2000 to 2021 for studies reporting resting EEG (rEEG) and transcranial magnetic stimulation combined with EEG (TMS-EEG) measures in patients undergoing MDD treatments. The search yielded 966 articles, 204 underwent full-text screening, and 51 studies were included for a narrative synthesis of findings along with confidence in the evidence. In rEEG studies, non-linear quantitative algorithms such as theta cordance and theta current density show higher predictive value than traditional linear metrics. Although less abundant, TMS-EEG measures show promise for predictive markers of brain stimulation treatment response. Future focus on TMS-EEG measures may prove fruitful, given its ability to target cortical regions of interest related to MDD.